2014
DOI: 10.1108/er-03-2013-0026
|View full text |Cite
|
Sign up to set email alerts
|

The double psychological contracts of temporary agency workers

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:198285 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 56 publications
3
24
0
1
Order By: Relevance
“…No significant relationship was found between the academic level of education and AC towards the client organization. These results are comparable with the results of Morf, Arnhold, and Staffelbach (2014). Also in their study, a significant negative relationship was found between highly educated TAWs and their commitment towards the employment agency, whereas this effect was not the case towards the client organization.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…No significant relationship was found between the academic level of education and AC towards the client organization. These results are comparable with the results of Morf, Arnhold, and Staffelbach (2014). Also in their study, a significant negative relationship was found between highly educated TAWs and their commitment towards the employment agency, whereas this effect was not the case towards the client organization.…”
Section: Discussionsupporting
confidence: 82%
“…With a primary focus on the client organization, TAWs may see the employment agency as an intermediate agent (cf. Morf, Arnhold, and Staffelbach 2014) that sometimes may even interfere with their relationship with the client organization, rather than an employer with which they can discuss OfCD. This latter explanation fits in with a 'traditional' perception of temporary work, with temporary workers being hired to cover short-term absence of permanent staff (cf.…”
Section: Overall Conclusionmentioning
confidence: 99%
“…Claes (2005) and Barringer and Sturman (1998) find that the fulfillment of each psychological contract is judged independently. However, Morf et al (2014) find there are spillover effects from the fulfillment of one psychological contract with another. Chambel and Fontinha (2009) find that the fulfillment of the psychological contract with the host positively influences fulfillment of the psychological contract with the agency.…”
Section: Psychological Contractsmentioning
confidence: 78%
“…These include feelings of powerlessness (Karkoulian et al, 2013) and job insecurity (Probst et al, 2018). Contingent workers may also struggle with a sense of divided loyalties between their employer and the organization at which they perform work (Liden et al, 2003;Barringer and Sturman, 1998), which in turn affects the psychological contracts with both of these entities (Chambel et al, 2016;Morf et al, 2014). Contingent workers also have the difficult decision of whether or not to engage in organizational citizenship behaviors (Feather and Rauter, 2004;Van Dyne and Ang, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the beneficial contributions of PCT to research on key issues in the field of expatriates/expatriation go beyond that field to connect with mainstream PC research, such as: the role of multiple foci to the PC (e.g. Bligh & Carsten, 2005;Morf, Arnold, & Staffelbach, 2014); variations in the established contract typology of relational and transactional to acknowledge other distinct elements (e.g. O'Donohue & Nelson, 2007;Scheel & Mohr, 2013); the involvement of people other than employee and employer in shaping the PC (Dabos & Rousseau, 2013;Ho, Rousseau, & Levesque, 2006); and the important implications of context in the development of PCs (e.g.…”
Section: Extant Research On Pcs and Expatriatesmentioning
confidence: 99%